A survey to evaluate knowledge, attitudes, and practices associated with the risk of foodborne infection in a sample of Sicilian general population - Emanuele Amodio; Giuseppe Calamusa; Salvatore Tiralongo; Federica Lombardo; Dario Genovese (AIMS Press, 2022)
Although foodborne infections contracted at home are frequent diseases worldwide, there is a general lack of information. Main purpose of this cross-sectional study was to evaluate knowledge, attitudes, and practices (KAP) of a sample of the general Sicilian population about the risk of contracting foodborne diseases. It was carried out through a web-based questionnaire to a Sicilian population sample. The questionnaire collected socio-demographic data, health issues, KAP and self-reported diseases. Scores were calculated for summarizing the results. A total of 373 subjects participated into the study. Overall, 65.15% of the participants were females, 48.26% of all respondents were aged between 18 and 29 years and over one-third were students (34.58%). At least one episode of vomiting/diarrhoea in the previous 3 months was reported by 119 respondents. Practices were associated with knowledge (R2 = 0.02; p < 0.01) and attitudes (R2 = 0.13; p < 0.001) although with low degree of correlation. A lower practice score was statistically significantly associated with both onset of foodborne transmitted infections in participants and among the cohabitants of participants. Our results confirm that foodborne disease can be strongly associated with food handling at home and with unsafe practices. Specific education on food safety could help to reduce the risk but the adoption of good practices of food manipulation is the real key to assure a reduction in food outbreaks in residences.